Surveillance Patterns After Curative-Intent Colorectal Cancer Surgery in Ontario - Jensen Tan; Jennifer Muir; Natalie Coburn; Simron Singh; David Hodgson; Refik Saskin; Alex Kiss; Lawrence Paszat; Abraham El-Sedfy; Eva Grunfeld; Craig Earle; Calvin Law (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Postoperative surveillance following curative-intent resection of colorectal cancer (CRC) is variably performed due to existing guideline differences and to the limited data supporting different strategies.